Acid-Stable Ester Linkers for the Solid-Phase Synthesis of Immobilized Peptides - Pícha, Jan; Buděšínský, Miloš; Mitrová, Katarína; Jiráček, Jiří (ChemPlusChem, 2020)
A series of N-terminally Fmoc-protected linkers of the general formula Fmoc-X-CO-O-Y-COOH have been prepared, where X is -NH-CH2 -CH2 - or -p-(aminomethyl)phenyl- and Y is -(CH2 )n - (n is 1 or 4) or -p-(methyl)phenyl-. These linkers can easily be covalently attached via their C-terminal carboxyl group to a resin bearing a free amino group. After cleavage of the N-terminal Fmoc group, the linkers can be extended by standard solid-phase peptide synthesis techniques. These ester linkers are acid-stable and resistant to the base-mediated diketopiperazine formation that often occurs during the synthesis of ester-bound peptides; they are stable at neutral pH in aqueous buffers for days but can be effectively cleaved with 0.1 m NaOH or aq. ammonia within minutes or hours, respectively. These properties make these ester handles well suited for use as linkers for the solid-phase peptide synthesis of immobilized peptides when the stable on-resin immobilization of the peptides and the testing of their biological properties in aqueous buffers at neutral pH are necessary.
Keywords: estery; peptides; diketopiperazines; Esters; Indicators and Reagents; techniky syntézy na pevné fázi; imobilizované proteiny; indikátory a reagencie; protecting groups; Solid-Phase Synthesis Techniques; solid-phase synthesis; Immobilized Proteins; Peptides; esters; peptidy